2014
DOI: 10.1155/2014/382959
|View full text |Cite
|
Sign up to set email alerts
|

Serratiopeptidase Niosomal Gel with Potential in Topical Delivery

Abstract: The objective of present study was to develop nonionic surfactant vesicles of proteolytic enzyme serratiopeptidase (SRP) by adapting reverse phase evaporation (REV) technique and to evaluate the viability of SRP niosomal gel in treating the topical inflammation. The feasibility of SRP niosomes by REV method using Span 40 and cholesterol has been successfully demonstrated in this investigation. The entrapment efficiency was found to be influenced by the molar ratio of Span 40 : cholesterol and concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…The right paw served as a reference of noninflamed paw for comparison. The percentage difference between right and left paw volumes was taken as percent edema produced (“as discussed by Shinde and Kanojiya [16]”). The percent edema produced with test samples was subtracted from percent edema produced in control group to obtain percent edema inhibition by respective groups.…”
Section: Evaluation Of Niosomal Formulationmentioning
confidence: 99%
“…The right paw served as a reference of noninflamed paw for comparison. The percentage difference between right and left paw volumes was taken as percent edema produced (“as discussed by Shinde and Kanojiya [16]”). The percent edema produced with test samples was subtracted from percent edema produced in control group to obtain percent edema inhibition by respective groups.…”
Section: Evaluation Of Niosomal Formulationmentioning
confidence: 99%
“…Therefore, a topical formulation of serratiopeptidase that potentially reduces adverse effects and increase local effects has been developed by Shinde and Kanojiya using niosomes. The results showed that the newly formulated serratiopeptidase niosomal gel had anti-inflammatory activity comparable to that of diclofenac gel [84].…”
Section: Inflammationmentioning
confidence: 90%
“…The stability studies of optimised midazolam loaded niosome (N5) and midazolam loaded niosomal transdermal patch (NT5) was done in the refrigerator (4±2 °C) and room temperature (30±2 °C)/65±5%RH for 90 d [94]. The optimised midazolam loaded niosome was subjected to particle size analysis which reviewed that there are no major variations in its stability in both room and refrigerator temperatures as illustrated in fig.…”
Section: Stability Studiesmentioning
confidence: 99%